Global city densities: Re-examining urban scaling theory - Burger, Joseph R.; Okie, Jordan G.; Hatton, Ian A.; Weinberger, Vanessa P.; Shrestha, Munik; Liedtke, Kyra J.; Be, Tam; Cruz, Austin R.; Feng, Xiao; Hinojo-Hinojo, César; Kibria, Abu S. M. G.; Ernst, Kacey C.; et al. (Frontiers in Conservation Science, 2022)
Understanding scaling relations of social and environmental attributes of urban systems is necessary for effectively managing cities. Heretonow, urban scaling theory (UST) has assumed that population density scales positively with city size. We present a new global analysis using a publicly available database of 933 cities from 38 countries. Our results showed that (18/38) 47% of countries analyzed supported increasing density scaling (pop ~ area) with exponents ~⅚ as UST predicts. In contrast, 17 of 38 countries (~45%) exhibited density scalings statistically indistinguishable from constant population densities across cities of varying sizes. These results were generally consistent in years spanning four decades from 1975 to 2015. Importantly, density varies by an order of magnitude between regions and countries and decreases in more developed economies. Our results (i) point to how economic and regional differences may affect the scaling of density with city size and (ii) show how understanding country- and region-specific strategies could inform effective management of urban systems for biodiversity, public health, conservation and resiliency from local to global scales.